798 Emergency Department Acute Urinary Retention Pathway Audit. (19th August 2022) - Collis, J; Pain, TM
Abstract: Aim: Establish if the Emergency Department (ED) acute urinary retention (AUR) pathway is being followed: Identify if digital rectal exams are being performed and residual volumes documented. Identify if Tamsulosin/Laxatives are prescribed Assess TWOC outcomes Method: Retrospective review of notes of patients coded as presenting with urinary retention in the ED between 01/02/2021 – 30/04/2021. Data collected from the hospital electronic patient system. Results: Total 147 patients coded for presenting to the ED with urinary retention. 64 patients removed as not applicable. 83 patients audited: 61 male and 22 female. 61 male patients analysed. A DRE was performed in 18% of those presenting with AUR. The residual volume was documented in 64%. Tamsulosin was started in 36%, not started in 36% and 16% were already on. Laxatives were started in 8%, not started in 69% and 16% were already on. TWOC was successful in 43%, unsuccessful in 21% and not applicable in 26% (E.g., Listed for TURP). A successful TWOC was achieved in 75% on both Tamsulosin and laxatives, 68% on Tamsulosin alone and 56% on neither. Conclusion: A DRE is not being regularly performed on initial presentation to the ED. Residual volumes are being more regularly recorded. The combination of Tamsulosin and laxatives provided the highest success rate for TWOC whilst not providing any medication provided the lowest. There is scope to increase adherence to the ED AUR pathway which may improve the rates of successful TWOC's and guide future management.